Adaptasi Mahasiswa Perantau di Kota Yogyakarta: Perspektif Teori Konstruksi Sosial Peter L. Berger - Anriani, Titi; Nasution, Khoiruddin (Huma: Jurnal Sosiologi, 2024)
One of the ways taken to develop oneself is to get out of the comfort zone by studying outside the city of birth or migrating, but this faces challenges in interacting because it finds a different situation from life in the place of origin. The purpose of the research is to find out the socioconstruction of migrant students according to Peter L. Berger's view. This research uses a qualitative approach with the research subjects being overseas students in the city of Yogyakarta. Data collection methods through observation, interviews and documentation. According to Peter L. Berger, reality is born along with knowledge, this happens due to the real social construction in human daily life. There are three stages of social construction according to Peter L. Berger, namely Externalization, Objectivation and Internalization. In the process of externalization, overseas students try to interpret and adapt to the language, customs and habits of the people of Yogyakarta in accordance with the stock of knowledge that exists in themselves. In this process, it appears that there are some students who have difficulty adjusting to the sociocultural environment in Yogyakarta. At the objectivation stage, overseas students try to understand and absorb the language, customs and habits of the people of Yogyakarta by discussing, forming study groups or cultural organizations that involve people from various backgrounds so that new knowledge and understanding of the life and habits of the people of Yogyakarta emerge. And this internalization process over time, the knowledge values that already exist in each overseas student from the results of objectivation are able to be manifested in actions, language, or expressions, so that overseas students are able to interact with the socio-cultural world of Yogyakarta. Further research needs to be done to explore the problems experienced by overseas students and how to overcome them from various perspectives.